PENERAPAN STRATEGI POINT COUNTERPOINT PADA PEMBELAJARAN PKn KELAS V DI MIN 13 BANJAR KABUPATEN BANJAR - Alya Soraya Isnani (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2017)
This study aims to determine the implementation of Point-Counterpoint strategy on learning VII C grade in MIN 13 Banjar District and the factors that influence the implementation of counterpoint strategy on learning VII C grade in MIN 13 Banjar District. Subject in the study was 1 teacher of civic education subject. Data collection techniques used in this study observation, interviews, and study documents. The data processing techniques used data reduction, data presentation, and data verification. Data that has been processed and interpreted then analyzed to descriptive qualitative. After that in taking the conclusion the author took the inductive method of conclusions that are specific to the general conclusions. From the results of this study can be concluded that the implementation of Point-Counteroint strategy on learning VII C grade in MIN 13 Banjar Regency in general is well done with the making of the lesson plan (or RPP) where the RPP made by the teacher in accordance with the steps of Point-Counterpoint strategy and at the time of execution of teaching in accordance with steps of Point-Counterpoint strategy. This can be known from the teacher's educational background, teacher experience, and adequate facilities and infrastructure.